1993
DOI: 10.1039/ft9938901823
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state transformation of SAPO-37 molecular sieve above 1100 K

Abstract: The changes occurring in SAPO-37 upon heating it to 1273 K are studied using 29Si, 27AI and 31P magic-anglespinning nuclear magnetic resonance (MAS NMR), X-ray diffraction (XRD) and infrared spectroscopy. The removal of the template at 873 K leads to a shift of both 29Si and 27AI MAS NMR peaks, suggesting an interaction of the template with some SiO, and AIO, tetrahedra. A further solid-state transformation is shown to occur between 1073 and 1173 K. This involves the formation of siliceous islands, generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…[20,21] Importantly, at high temperatures the H-SAPO framework can be (locally) separated into silicon domains and the AlPO 4 phase. [20,22] This transformation, which can take place during the oxidative treatments applied to regenerate the MTH catalysts, might induce significant changes in their physicochemical properties. More specifically, it has been reported that the formation of silicon islands leads to a reduction in the number of acid sites available for the MTH reaction and increases the acid strength of the Si-OH-Al species located at boundaries of the H-SAPO and the silicon island phases.…”
Section: Physicochemical Changes By Applying a Severe Hydrothermal Trmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] Importantly, at high temperatures the H-SAPO framework can be (locally) separated into silicon domains and the AlPO 4 phase. [20,22] This transformation, which can take place during the oxidative treatments applied to regenerate the MTH catalysts, might induce significant changes in their physicochemical properties. More specifically, it has been reported that the formation of silicon islands leads to a reduction in the number of acid sites available for the MTH reaction and increases the acid strength of the Si-OH-Al species located at boundaries of the H-SAPO and the silicon island phases.…”
Section: Physicochemical Changes By Applying a Severe Hydrothermal Trmentioning
confidence: 99%
“…This observation is in line with previous studies performed on H-SAPO-34 materials and indicates a redistribution of silicon atoms occurring at high steaming temperatures. [22,27] Complementary to the 29 Si MAS NMR experiments, 27 Al MAS NMR measurements on the SAPO-34-C and SAPO-34-S molecular sieves were performed. As presented in Figure 3 b, the spectrum of SAPO-34-C is characterized by peaks at around d = 60-50 and 0 ppm, indicative for the presence of a mixture of 4and 6-fold aluminum coordinated species, respectively.…”
Section: Physicochemical Changes By Applying a Severe Hydrothermal Trmentioning
confidence: 99%
“…Presence of such lattice has never been previously observed or stated for SSZ-39 (or isostructural zeolites) although isostructural zeolite SAPO-18, for example, has been studied with electron microscopy [28]; we note that the presence of incommensurate lattice may potentially be one of the factors contributing to such high stability of this material, because such lattice modulations have not been observed for SSZ-13 material (built of the same structural units and having essentially the same crystallographic density as SSZ-39): this point needs further investigation. However, as has been previously demonstrated in the pioneering studies by Derewinski, Barthomeuf and co-workers [29][30][31][32], the enhanced thermal stability of the larger zeolite crystals compared with nanosized analogues is the consequence of the absence of highindex facets and presence of mostly low-index facets having lower surface energy and thus increased thermal stability. It was also demonstrated that structure of another SAPO material i.e.…”
Section: Pna Performance Of Hydrothermally Aged Pd/ssz-39 Materialsmentioning
confidence: 77%
“…The combination of the SM2 and SM3 mechanisms leads to the formation of silicon aggregates or "silicon islands" [8]. Silicon islands are formed when at least two adjacent T sites are occupied by silicon [9,10], [11].…”
Section: Scopementioning
confidence: 99%